L’effet de l’information sur le marché du travail dans le processus décisionnel relatif au choix de carrière. - Savard, Réginald; Michaud, Guylaine; Bilodeau, Cynthia; Arseneau, Sylvie (Canadian Journal of Counselling and Psychotherapy, 2008)
Research on labour market information (LMI) and career development highlights the importance and utility of such information. However, the effects of that information on career development are less significant if the information is not delivered by a counsellor. Studies show that individuals researching LMI are essentially guided by their interests and have a tendency to overlook other important information which could help clarify their career choices. The quantity and quality of the information must also be considered in how effectively it is processed. Finally, the degree of cognitive complexity required to process the information available places demands on the individual in its integration.